2021
DOI: 10.1152/ajpregu.00063.2021
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 stimulates the hypothalamus-pituitary-interrenal axis hormones in goldfish

Abstract: Stress in vertebrates is mediated by the hypothalamus-pituitary-adrenal [in mammals]/interrenal [ in fish] (HPA/I) axis, which produces the corticotropin releasing factor (CRF), adrenocorticotropic hormone (ACTH) and corticosteroids, respectively. Nesfatin-1, a novel anorexigenic peptide encoded in the precursor nucleobindin-2 (NUCB2), is increasingly acknowledged as a peptide that influences the stress axis in mammals. The primary aim of this study was to characterize the putative effects of nesfatin-1 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Previous studies from our lab also showed that NESF-1 is a stress-responsive peptide that stimulates stress-related hypothalamus-pituitary-interrenal [HPI; similar to mammalian HPA tissues] axis hormones in goldfish 2 . Moreover, NESF-1 was shown to directly stimulate the synthesis of ACTH precursor in mouse pituitary corticotrophs 1 .…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Previous studies from our lab also showed that NESF-1 is a stress-responsive peptide that stimulates stress-related hypothalamus-pituitary-interrenal [HPI; similar to mammalian HPA tissues] axis hormones in goldfish 2 . Moreover, NESF-1 was shown to directly stimulate the synthesis of ACTH precursor in mouse pituitary corticotrophs 1 .…”
Section: Introductionmentioning
confidence: 65%
“…Given that NUCBs are DNA binding proteins 1 , the staining found in the nucleus is reflective of that role. NUCB1/NLP-like immunoreactivity was reported in the central nervous system and peripheral tissues, including endocrine cells of the anterior pituitary of rats and mice 1 , 28 , mouse insulinoma MIN6 cell line and mouse pancreatic beta cells 17 as well as testis, ovary, and head kidney interrenal cells 2 and pituitary of goldfish 18 . The results reported here show that human adrenal cortex cells express NUCB peptides and possibly other bioactive peptides residing within it, which may act directly on these cells to regulate the steroidogenesis pathway and cortisol synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesfatin-1 and Nlp are key players in the regulation of growth [3,15], feeding [1,2,7,16], reproduction [4,5,8], heart function [6,17], and hormone secretion [3][4][5][8][9][10]15,18] in fish and mammals. Overall, nesfatin-1 and Nlp are multifunctional peptides with tissue-specific, hormone-like actions in fish and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a general suppressive effect for nesfatin-1 on Gh-Igf axis in goldfish. Meanwhile, nesfatin-1 stimulated both pituitary adrenocorticotrophic hormone (Acth) and cortisol in vivo in goldfish [9]. The suppressive role of nesfatin-1 on serum luteinizing hormone (Lh) and Lh beta and follicle-stimulating hormone (Fsh) beta mRNA was also reported in goldfish [5].…”
Section: Introductionmentioning
confidence: 91%